2020
DOI: 10.1002/mdp2.202
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable nanofibers in tissue engineering and biomedical applications

Abstract: The practice of using a massive amount of environmental unfriendly and toxic petroleum-based materials in tissue engineering and biomedical fields demands the materials, which are biodegradable, renewable, environmentally friendly, biocompatible, and bioactive. So, renewable polymers have got considerable attention due to their numerous desirable properties. The nanofibers that are prepared from renewable materials and their blends can integrate the properties of both nanofibers and renewable polymers. Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 203 publications
(193 reference statements)
0
11
0
Order By: Relevance
“…Chemical (acetylation, alkaline, benzoylation, peroxide, potassium permanganate, silane, and stearic acid) and surface treatments [1] Non-electrospinning techniques (i.e., phase separation, drawing, template synthesis, and self-assembly), electrospinning, and hydrothermal techniques [35][36][37][38]…”
Section: Main Treatments For Natural Fibers Main Fabrication Techniques Of Nanofibersmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical (acetylation, alkaline, benzoylation, peroxide, potassium permanganate, silane, and stearic acid) and surface treatments [1] Non-electrospinning techniques (i.e., phase separation, drawing, template synthesis, and self-assembly), electrospinning, and hydrothermal techniques [35][36][37][38]…”
Section: Main Treatments For Natural Fibers Main Fabrication Techniques Of Nanofibersmentioning
confidence: 99%
“…Several studies reported about different applications of the nanofibers in medical sectors, such as Malik et al [37], de 6. The healing process of bones and tendons is very slow, and The application of nanofibers or with some bioactive compounds is increasing in medicine as drug release capsule; transdermal absorbent; drug release artificial skin; wound dressing; artificial blood vessel; covered stent; artificial cornea; artificial skin; filling agent for artificial bone, wound, and therapeutic applications; nerve or organ patch wound covering and protective agent; dialysis membrane; surgical adhesive sheet; and adhesion prevention materials [63].…”
Section: Nanofibers For Biomedical Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofibers are nanotechnological products, which could be defined as one-dimensional nanomaterials whose diameter range from tens to hundreds of nanometers and are produced using a broad range of natural, synthetic, and hybrid polymers (Bose 2021). The main methods for producing the nanofibers may include nonelectrospinning techniques (i.e., phase separation, template synthesis, drawing, and self-assembly), electrospinning and hydrothermal techniques (Malik et al 2020;Naidu et al 2021). Nanofibers have many benefits that can use in several fields in our life (Table 1).…”
Section: Applications Of Nanofibers In Agriculturementioning
confidence: 99%
“…Over the past decades, significant efforts have been dedicated to replicating the mechanical integrity, morphology, and architecture of real natural human tissue, particularly by developing new preparation techniques and reinforcing protein-based scaffolds with nanomaterials that mimic native tissue environments to improve tissue growth, differentiation, proliferation, cellular signaling, etc. The introduction of nanofibers, nanoparticles, nanotubes, or other inorganic carriers [25][26][27][28] was found to be highly efficient for mediating tissue formation.…”
Section: Introductionmentioning
confidence: 99%